2016
DOI: 10.1139/cgj-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale successive boulder impacts on a rigid barrier shielded by gabions

Abstract: Debris flows occur in multiple surges. Boulders entrained within the flow have been reported to incapacitate structures within its flow path. Single-layer cushions, such as gabions, are often installed to shield debris-resisting barriers from boulder impact. However, most relevant works only focus on single impact and the performance of gabions subjected to successive loading is still not well understood. A new large-scale pendulum facility was established to induce impact energy of up to 70 kJ on an instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…Such fronts are highly inertial, potentially incapacitating structures along their flow path and claiming lives (Hungr & Evans, 1988;Ng et al, 2016). Zhang et al (1996) reported a boulder-rich debris flow front impacting a reinforced concrete bridge pier on the Chengdu-Kunming Railroad in China, destroying the pier and causing 220 fatalities.…”
mentioning
confidence: 99%
“…Such fronts are highly inertial, potentially incapacitating structures along their flow path and claiming lives (Hungr & Evans, 1988;Ng et al, 2016). Zhang et al (1996) reported a boulder-rich debris flow front impacting a reinforced concrete bridge pier on the Chengdu-Kunming Railroad in China, destroying the pier and causing 220 fatalities.…”
mentioning
confidence: 99%
“…en, the dynamic behavior of dry granular flows toward barriers has been further studied [9,13,[22][23][24]. In the studies, some more critical influence mechanisms were revealed, such as the formation of dead zones [21,25] and run-ups [26,27]. e dead zones allow momentum to run-up vertically along the barrier [28], and the run-ups reduce the load on the top of the barrier and increase the impact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the change in the bulk stiffness of the cushion layer due to compaction under successive impacts (ASTRA 2008) is often ignored in current design. Ng et al (2016) demonstrated that the reduction of impact loads rely predominantly on the irreversible rearrangement of rock fragments. The mechanism of crushing in gabion cushioning layers strongly depends on the mechanical properties of the rock and their size (Lambert et al 2009).…”
mentioning
confidence: 99%
“…Generally, the particle sizes of the rock fragments used to construct gabion cushion layers range from 160 to 300 mm (GEO 1993;Ng et al 2016). Zhang et al D r a f t (2016) and Su et al (2018) both showed that the transmitted load on a rigid barrier which is shielded by a cushion layer comprising rock fragments (rock-filled gabions) decreases with the particle size, although particle crushing was not considered in these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation